2016
DOI: 10.1038/srep32271
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex gene editing via CRISPR/Cas9 exhibits desirable muscle hypertrophy without detectable off-target effects in sheep

Abstract: The CRISPR/Cas9 system provides a flexible approach for genome engineering of genetic loci. Here, we successfully achieved precise gene targeting in sheep by co-injecting one-cell-stage embryos with Cas9 mRNA and RNA guides targeting three genes (MSTN, ASIP, and BCO2). We carefully examined the sgRNAs:Cas9-mediated targeting effects in injected embryos, somatic tissues, as well as gonads via cloning and sequencing. The targeting efficiencies in these three genes were within the range of 27–33% in generated lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 41 publications
1
74
0
2
Order By: Relevance
“…In this study, the ADG in mutant goats was 36% higher than that in WT goats (145 vs. 107 g) from D0 to D360, indicating that the growth rate of mutant goats was much higher than that of control goats, which is consistent with the ADG results of MSTN ‐edited sheep in our recent study (Wang et al . ). The BW of gene‐modified goats is significantly higher than that of several goat breeds in early growth stages, including at birth or weaning (Mahgoub & Lodge ; Mohammed & Amin ).…”
Section: Discussionmentioning
confidence: 97%
“…In this study, the ADG in mutant goats was 36% higher than that in WT goats (145 vs. 107 g) from D0 to D360, indicating that the growth rate of mutant goats was much higher than that of control goats, which is consistent with the ADG results of MSTN ‐edited sheep in our recent study (Wang et al . ). The BW of gene‐modified goats is significantly higher than that of several goat breeds in early growth stages, including at birth or weaning (Mahgoub & Lodge ; Mohammed & Amin ).…”
Section: Discussionmentioning
confidence: 97%
“…By employing the CRISPR/Cas9 system, we successfully generated gene‐modified Tan sheep (Wang et al . ). Cas9 mRNA and two sgRNAs targeting exon 2 of the BCO2 gene were microinjected intracytoplasmatically into one cell stage sheep zygotes (Fig.…”
Section: Sequencing Analysis Summary Of Biopsied Sheep Adipose Tissuesmentioning
confidence: 97%
“…a, Table S1), which were collected surgically from naturally mated sheep as previously described by Wang et al . (). We were able to obtain a total of 10 Tan sheep with the BCO2 gene disrupted.…”
Section: Sequencing Analysis Summary Of Biopsied Sheep Adipose Tissuesmentioning
confidence: 97%
See 1 more Smart Citation
“…The knockout lambs were 25% heavier [7] and maintained the same wool quality traits than Merino lambs (unpublished data). Although this proof of concept did not include the study of the offspring, in following studies germline transmission of MSTN mutation have been reported by its presence in the gonads of founders (in sheep [46] and goats [47]) and offspring [47]. Amazingly, these early studies suggested that what farmers have pursued for centuries (i.e., animals producing both high-quality wool and more meat), might be achieved by CRISPR in few months.…”
Section: Improving Productive Traitsmentioning
confidence: 99%